PROMISE: A Model of Insight and Equanimity as the Key Effects of Mindfulness Meditation - Eberth, Juliane; Sedlmeier, Peter; Schäfer, Thomas (Frontiers in Psychology, 2019)
In a comprehensive meta-analysis on the effects of mindfulness meditation, Eberth and Sedlmeier (2012) identified a multitude of positive effects that covered a wide range of psychological variables, such as heightened mindfulness as measured through contemporary mindfulness scales, reduced negative emotions, increased positive emotions, changes in self-concept, enhanced attention, perception, and wellbeing, improved interpersonal abilities, and a reduction of negative personality traits. The present research aimed at developing and testing a comprehensive model explaining the wide range of mindfulness meditation effects and their temporal and causal relationships. In Study 1, interviews with meditators at different levels of experience were analyzed using a grounded theory procedure. The resulting model was triangulated and refined by concepts from both Western research and ancient Buddhist scriptures. The model developed highlights equanimity (reduction in emotional reactivity) and insight (alteration of cognitions) as the two key effects of mindfulness meditation that eventually lead to increased wellbeing. The model was pilot-tested with a large sample of meditators and non-meditators in Study 2. Data showed an acceptable fit with the model and indicated that meditators and non-meditators score significantly differently on the model’s core categories.